Pengujian Viabilitas Dan Vigor Benih Beberapa Jenis Tanaman Yang Beredar Di Pasaran Kota Ambon - M.K Lesilolo; Johan Riry; E.A Matatula (Agrologia, 2013)
This study aims to identify and determine the viability and vigor of seeds of some species of plants in Ambon city market. This research was conducted in the Laboratory of Seed Control and Certification Institute (BPSB) Passo and at the Faculty of Agriculture, University of Pattimura Greenhouse Ambon from February to April 2012. The method used was testing seed with duplo system and using T test with three replications. There were eight seed plant types tested, i.e corn, mustard, long bean, eggplant, bitter melon, cucumber, large chili, and cabbage. Responses observed consisted of viability parameters, i.e. germination percentage, germination rate, and germination rate index, and vigor parameters consisted of simultaneity sprouted seeds and sprouted seeds pace. The results showed that seeds in the market city of Ambon, such as corn, mustard, long beans, eggplant, bitter melon, cucumber, large chili, and cabbage were in excellent quality, as shown by the results of the seed germination rate which reached 90.33 - 97.33% at laboratory test, meanwhile at greenhouse test the rate reached 90.33 - 94.33%, strong vigor with synchrony seed grow were 51.00 - 64.67%, and the growth rate reached 29.46 - 33.65%.